St. Kitts and Nevis : 2015 Article IV Consultation-First Post-Program Monitoring Program Monitoring Discussions-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2015)
This 2015 Article IV Consultation highlights that the economic situation of St. Kitts and Nevis has continued to improve since the completion of the IMF-supported home-grown economic program in July 2014. Continued rapid inflows under the Citizenship-By Investment program have led to a surge in construction activity, and supported a large increase in government and Sugar Industry Diversification Fund investments and spending, including on the People Employment Program. These factors, together with the ongoing recovery in tourist arrivals fueled rapid GDP growth of about 6 percent in 2013 and 2014. The near-term outlook remains strong, but there are risks on the horizon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet